การจัดการเรียนรู้แบบร่วมมือเทคนิค TGT เรื่อง สถิติ สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 2 - Thongcharern, Suwanan; Yonwilad, Wannatida; Hembasat, Ponpitak; Pimpasalee, Wannapol (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The purposes of the research were to 1) develop students’ learning achievement on statistics with the cooperative learning TGT technique such that the students could gain a mean score not less than 70 percent of the full score and at least 70 percent of all students passed the criterion, 2) compare the learning achievement on statistics before and after the intervention, and 3) explore the student satisfaction with the developed learning management. The sample of this study, obtained through purposive sampling, consisted of 19 Mathayomsuksa 2 students studying at Song Plueai Witthayayon School in the second semester of the academic year 2021. The research instruments included 1) six lesson plans on statistics based on the cooperative learning TGT technique, 2) a 20-item, 4-option multiple-choice learning achievement test on statistics, and 3) a student satisfaction questionnaire. Data were analyzed using percentage, mean, standard deviation, and t-test for Dependent Samples. The research findings showed that 1) the students’ learning achievement outcome achieved 79.20 percent of the full score and 78.95 percent of the students passed the desired criterion, 2) the students’ learning achievement after the intervention was higher than that before the intervention at the .05 level of significance, and 3) the student satisfaction with the developed learning management was at the highest level.